2010
DOI: 10.1007/s12192-010-0202-1
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol regulates multiple nuclear transcription factors belonging to HSP90's clients in a dose- and cell type-dependent way

Abstract: Celastrol, a novel HSP90 inhibitor, has recently attracted much attention due to its potential in multiple applications, such as anti-inflammation use, degenerative neuron disease relief, and tumor management. At present, the studies in celastrol's effects on HSP90's clients have focused on the kinase sub-population, while another key sub-population, nuclear transcription factors (TFs), is not being well-explored. In this study, we observe the effects of celastrol on 18 TFs (belonging to HSP90 clients) in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Although several reports mentioned about the involvement of celastrol in apoptosis of hepatoma cells, no study has been reported the anti-metastatic function of celastrol in HCC [25,26]. In this study, we investigated the effect of celastrol on migration and invasion ability of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports mentioned about the involvement of celastrol in apoptosis of hepatoma cells, no study has been reported the anti-metastatic function of celastrol in HCC [25,26]. In this study, we investigated the effect of celastrol on migration and invasion ability of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it was very confusing that Rottlerin was positive with metformin in our result, because Rottlerin could inhibit insulin-stimulated glucose transport in 3T3-L1 adipocytes by uncoupling mitochondrial oxidative phosphorylation [41]. Besides, Zhang et al suggested new possible applications (drug repositioning) for Celastrol, such as diabetes management [42]. …”
Section: Resultsmentioning
confidence: 94%
“…The in vivo anti-inflammatory effects of this triterpene have been demonstrated in animal models of collagen-induced arthritis, rheumatoid arthritis, Alzheimer's disease, asthma, and systemic lupus erythematosus [83][84][85]. This triterpene has also been found to suppress tumor initiation, promotion and metastasis in various cancer models through modulation of multiple pro-inflammatory cytokines, chemokines, enzymes and transcription factors [4,[86][87][88][89][90][91]. For example, celastrol has been shown to inhibit the proliferation of a wide variety of tumor cells [6,83,[92][93][94].…”
Section: Celastrolmentioning
confidence: 98%